STUDI TENTANG SALUAK PENGHULU DI KOTA PAYAKUMBUH - SARI, DINA HERLINA; Adriani, Adriani; Idrus, Yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aimed to describe the design, opportunity, how to use, and meaning-making technique saluak prince in Payakumbuh. This research is descriptive qualitative. Data were analyzed with a snow ball sampling technique. Data collection techniques using observation, interviews and documentation. Results of the study revealed that: 1) Design saluak prince in Payakumbuh have folds in the same direction at the front of the number eight, the color is the color of batik material with rigid texture, dull and not transparan2) Saluak prince in Payakumbuh imposed primarily on traditional ceremonies and events adat3 ) Saluak prince in Payakumbuh imposed in accordance with the level of ninik mamak4) saluak making techniques include providing material starch, until the formation of saluak5) saluak meaning prince in Payakumbuh City like a big tree that symbolizes the duties and responsibilities of the prince. Kata Kunci: saluak, penghulu.